Improving Production Ramp-Up Through Human Resource Methods. Issue 1 (1st January 2016) - Heine, Ina; Beaujean, Patrick; Schmitt, Robert; Aachen, Rwth
Abstract : This article provides an overview of selected human resource (HR) methods that have implications for the management of ramp-up phases. Based on the specific challenges within production ramp-up, the following six HR methods and corresponding instruments are outlined: knowledge management, competency modeling, reward systems, leadership development, employee selection, and team development. Each method is briefly described and suggestions within the context of ramp-up management are provided. This overview supports ramp-up managers' selection of HR methods that have the higher goal of improving ramp-up performance. However, the practical implications of these HR methods are not clear, because empirical literature about the application of HR methods within the context of production ramp-up is limited. Further empirical research on the effects of specific HR methods on ramp-up performance, as well as detailed descriptions of the respective application and related expenses, are required to understand and evaluate their contribution.